Where does capital flow : a comparison of US States and EU Countries 1950 - 2000 - Kalemli - Ozcan, Sebnem; Sorensen, Bent E.; Turan, Belgi; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
We nd that the United States in the 1950s and 1960s was characterized by strong \catch-up growth" in the south with capital owing from rich northern states to poorer southern states|consistent with the predictions of the simple neoclassical model. After the 1970s, \catch-up growth" is mainly over in the United States and capital is owing to productive (rich) states. For Europe, we nd that capital has been owing from the richer countries to the poorer countries since the 1970s with no signs yet of the \catch-up" phase having run its course, except for the country of Ireland.
Economic Papers